Hubungan Motivasi Belajar Instrinsik Terhadap Prestasi Belajar Biologi Kelas XI IPA di SMA Negeri 4 Tanjungpinang - Muhamad Kukuh Handoko; Nevrita; Nurul Asikin (Pedagogi Hayati, 2019)
Abstract: This type of correlation research is a type of research that discusses the relationship between one or two variables in the study. In this study, the researchers looked at the level of the relationship between intrinsic learning motivation towards biology learning achievement of students of class XI science in SMA 4 Tanjungpinang. In this study, researchers used a sample of research consisting of students and students from class XI IPA 1 to class XI IPA 5, amounting to 84 students. The data collection techniques in this study used two research instruments, namely questionnaire and question instruments. The questionnaire instrument was used to measure the value of intrinsic learning motivation while the test instrument was used to measure student learning achievement. Based on the results of the Pearson product moment test, the significance direction is 0.00, meaning that there is a correlation between the above variables, then, the relationship between intrinsic learning motivation towards learning achievement produces a value of 0.50 which is categorized into medium correlation. Then it can be concluded that the above hypothesis is accepted. Abstrak: Penelitian ini bertujuan untuk mengetahui tingkat hubungan antara motivasi belajar instrinsik terhadap prestasi belajar biologi siswa kelas XI IPA di SMA Negeri 4 Tanjungpinang. Dalam penelitian ini, peneliti menggunakan sampel penelitian yang terdiri dari siswa dan siswa dari kelas XI IPA 1 sampai kelas XI IPA 5 yang berjumlah 84 orang siswa. Adapun teknik pengumpulan data dalam penelitian ini menggunakan dua instrument penelitian yaitu instrument angket dan soal. Instrument angket digunakan untuk mengukur nilai motivasi belajar instrinsik sementara instrument tes digunakan untuk mengukur prestasi belajar siswa. Berdasarkan hasil analisis uji pearson product moment, arah signifikasinya bernilai 0,00 artinya terdapat korelasi antara variabel di atas, selanjutnya, tentang hubungan antara motivasi belajar instrinsik terhadap prestasi belajar menghasilkan nilai sebesar 0,50 yang dikategorikan ke dalalm korelasi sedang. Maka dapat diambil kesimpulan bahwa hipotesis di atas diterima.